Outcomes of fractional flow reserve‐guided percutaneous coronary interventions in patients with acute coronary syndrome. Issue 2 (29th November 2019) - Omran, Jad; Enezate, Tariq; Abdullah, Obai; Al‐Dadah, Ashraf; Walters, Daniel; Patel, Mitul; Reeves, Ryan; Mahmud, Ehtisham
Abstract: Introduction: Fractional flow reserve (FFR) assessment has been validated as an effective tool to guide revascularization of stable coronary artery disease. The role of utilizing FFR in acute coronary syndrome (ACS) is less established. Methods: The study population was extracted from the National Readmissions Data (NRD) 2014 using International Classification of Diseases, ninth edition, clinical modification (ICD‐9‐CM) codes for ACS, percutaneous coronary intervention (PCI), FFR, and periprocedural complications. Study endpoints included all‐cause of in‐hospital mortality, length of index hospital stay (LOS), acute kidney injury (AKI), bleeding, coronary dissection, total number of stents used, stroke, vascular complications (VCs), and the total charges of index hospitalization. Results: A total of 304, 548 discharges that had the diagnosis of ACS and treated invasively within the same index hospitalization (average age 65.1 years; 64% male) were identified. Among these, 7, 832 had FFR guided invasive treatment (2.6%) which was associated with significantly lower in‐hospital all‐cause mortality (1.1 vs. 3.1%, p  < .01), shorter LOS (4.6 vs. 5.3 days, p  < .01), less AKI (12.5 vs. 14.6%, p  < .01), less bleeding (7.0 vs. 8.5%, p  < .01), and lower total charges ($99, 805 vs. $105, 736). There was no significant difference between both groups in terms of stroke (2.2 vs. 2.3%, p = .41), coronary dissection (0.7 vs. 0.8%, p = .34), VC (1.3 vs. 1.0% p = .01) or the total number of stents used (55.5 vs. 54.5% p = .34). Conclusion: In patients presenting with an ACS FFR‐ guided PCI, as compared to angiography guided PCI, was associated with lower rates of in‐hospital mortality, shorter LOS, less AKI, bleeding and lower hospital charges. There was no significant difference in terms of the incidence of stroke, coronary dissection, VC or the total number of stents used.